Analysis of the Role of Premarital Guidance in Building Adolescents' Marriage Readiness: Study in Liunggunung Village, Purwakarta Regency, Indonesia - Widyastuti, Dwi (Arkus, 2024)
Marriage is one of the important events in human life. Therefore, marriage readiness is an important thing to pay attention to, especially for teenagers. Premarital guidance is one effort to increase teenagers' marriage readiness. This research aims to analyze the role of premarital guidance in building adolescent marriage readiness in Liunggunung Village, Purwakarta Regency, Indonesia. This research uses a qualitative approach with a case study method. The research subjects were 10 teenagers who had attended premarital guidance in Liunggunung Village. Data was collected through in-depth interviews and observations. The research results show that premarital guidance plays an important role in building teenagers' marriage readiness. Premarital guidance provides the knowledge and skills that teenagers need to get married, such as understanding marriage, husband-wife relationships, communication, and financial management. Premarital guidance also helps teenagers to prepare themselves physically and mentally for marriage.